A study on self-reported food allergy in young adults from various colleges in Kerala, India - Dias, Renata Ann; Mundodan, Jenyz M.; M. V., Sruthi (International Journal Of Community Medicine And Public Health, 2019)
Background: Food allergy is defined as a reproducible adverse immune reaction to food proteins. Food allergies can result in life threatening reactions and diminish quality of life. In the last several decades, prevalence of food allergy has increased in several regions throughout the world. Methods: A cross sectional study was conducted among 321 young adults of the age 17 to 26 years from various colleges in Kerala. The participants were asked to fill out a pretested questionnaire. The data was collected and entered in MS Excel and analyzed. Results: Adverse reactions following food consumption was experienced by 82 respondents (25.5%). Out of these 82 respondents, 38 (46%) had their condition diagnosed by a doctor. 23 respondents had only one episode of such an attack. 41 respondents took medications for the attack. 14 respondents had been hospitalized at least once for such an attack. The most common symptoms following the consumption of food were as follows: vomiting, itching and eczema. The symptoms occur after the consumption of sea food/fish and eggs mostly. 27 respondents had a family history of food allergy. Conclusions: The symptoms of food allergy may vary from minor itching to even anaphylaxis. It is very important to know the causative allergen in the diet to prevent the occurrence of an episode of food allergy.